Increased overwintering temperature reduces reproductive success of the solitary bee species Osmia bicornis - Sarah Müller; Jana Collatz; Henning Richter; Robert Zboray; Matthias Albrecht (Scientific Reports)
Abstract Solitary wild bees play a key role as pollinators of wild plants and crops, but they are increasingly at risk from anthropogenic global change, such as climate warming. However, how warmer temperature during overwintering affects reproductive success of those bees remains largely unknown. In a semi-field experiment we assessed individual life-long reproductive success of 144 females of the solitary bee species Osmia bicornis that had been wintered at three different temperatures. Overwintering mortality of bees was on average 32% higher at winter temperatures of 8 °C compared to 4.5 °C–0 °C, at which almost all bees successfully emerged. After wintering at 4.5 °C and 8 °C females produced less offspring than after overwintering at 0 °C (26% or 36% less offspring, respectively). Although longevity and daily offspring production rate were not significantly affected, nesting duration of females wintered at 0 °C tended to be longer (+ 2.5 days) than that of bees wintered at 4.5 °C, which likely contributed to the higher offspring production at colder overwintering temperatures. Mortality and sex ratio of offspring was not significantly affected. While future studies should also consider climatic variation during winter, these findings indicate that increasing mean overwintering temperatures could threaten O. bicornis and potentially other solitary bee populations.